Peru and Mexico: The Limited Effectiveness of Inter-American Court Rulings in Cases of Enforced Disappearance - Noriega Zamudio, José Jafet (2025)
This article, based on a qualitative methodology, examines all rulings issued by the Inter-American Court of Human Rights on enforced disappearance—both condemnatory judgments and compliance supervision decisions—complemented by a documentary review of specialized doctrinal sources. Its aim is to assess the effectiveness of the implementation of these rulings by analyzing the reparative measures ordered to the States of Peru and Mexico. It also addresses the contexts in which these crimes have occurred, identifying persistent patterns of state resistance and governmental indifference to international obligations. From this perspective, it explores the structural causes of non-compliance and proposes alternatives to foster a more effective implementation of the conventional commitments undertaken, in pursuit of justice and the comprehensive reparation of victims.